توثيق المجاهيل عند الإمام ابن حبان البستي: دراسة تطبيقية - باي، يونس (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The purpose of this study is to investigate the documentation of unknown narrators by Imam Ibn Hibban as well as extraction of their Hadiths in his authentic source (Sahih) in literature and practice. In order to fulfil this purpose we collected a sample of unknown narrators and investigate their persons and narrations. The importance of this study lies in taking this matter from ambiguity to clarity to render it easy for us to understand. In addition, The study carries within its folds some responses to those who accused Ibn Hibban of leniency towards unknown narrators or disrespected him by means of slander. In order to achieve the desired results, the study adopted many scientific approaches. First, The inductive approach where we collected scientific materials consisting of definitions, translations and sayings of scholars. Second, the sayings of scholars were examined and uncovered by employing the analytical approach. Third, Comparative approach was employed, where we made comparison between the sayings of scholars, their results and judgments they made. Fourth, Using the applied approach we collected unknown narrators and what they have narrated as reported by Ibn Hiban in his authentic source. The study has arrived to the following results: The narrators that have been adjudged by Ibn Hibban with anonymity have no existence in his authentic source as Ibn Hibban is known by his commitment to the conditions outlined by him. as a result, Ibn Hibban was not lenient; instead he loosed his condition yet adhered to it. However, The Hadiths of the unknown that he has extracted in his authentic source are not agreed upon solely by him, They have been agreed upon by some other Hadith scholars in their extraction. It is not fair to blame him alone.